2012
DOI: 10.1111/j.1442-2042.2012.03126.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrathecal administration of E‐series prostaglandin 1 receptor antagonist in a cyclophosphamide‐induced cystitis rat model

Abstract: Abbreviations & Acronyms BOO = bladder outlet obstruction CMG = continuous cystometrogram CYP = cyclophosphamide DRG = dorsal root ganglia EDTA = ethylenediaminetetraacetate EP = E-series prostaglandin EP1 = E-series prostaglandin 1 GAPDH = glyceraldehyde-3-phosphate dehydrogenase IC = interstitial cystitis ICI = intercontraction interval i.t. = intrathecal NSB = non-specific binding OAB = overactive bladder PGE2 = prostaglandin E2 RT-PCR = reverse transcription polymerase chain reaction TA = total activity Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Five ml of conjugate was added to TA well and 200 µL of Ellman's reagent was added to each well. PGE2 concentration was determinedd after absorbance measurement at 405 nm with a microplate reader (BIO-TEK, μQuant, USA) [24].…”
Section: Methodsmentioning
confidence: 99%
“…Five ml of conjugate was added to TA well and 200 µL of Ellman's reagent was added to each well. PGE2 concentration was determinedd after absorbance measurement at 405 nm with a microplate reader (BIO-TEK, μQuant, USA) [24].…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of Aδ fibres suggests that they are potentially involved in PGE 2 -induced pathophysiological states, such as urinary frequency and urgency in OAB, as well as C fibres. It has been shown that the dorsal root ganglion neurons innervating the urinary bladder express mRNAs encoding PGE 2 receptors, including EP1 (Wada et al 2013) and EP3 (Su et al 2008), both of which are G protein-coupled E-series prostaglandin (EP) receptors. Blockade of the EP3 receptor specifically attenuated firing of fibres with a slower CV and a higher firing threshold (i.e.…”
Section: Modulation Of Afferent Fibres By Pgementioning
confidence: 99%
“…In rats with bladder outflow obstruction, intravenous administration of an EP1 antagonist showed an increase in micturition intervals and a decrease in NVCs . In cystitis model rats, the expression of spinal EP1 receptors was upregulated, and intrathecal administration of an EP1 receptor antagonist prolonged ICI . Thus, it is likely that EP1 receptors contribute to LUT dysfunction under pathological conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Intravenous administration of an EP1 receptor antagonist increased micturition intervals and decreased non‐voiding contractions (NVC) in rats with bladder outlet obstruction . Our previous study using cystitis rats also demonstrated that intrathecal administration of an EP1 antagonist increased the micturition interval . Thus, we hypothesized that PGE2 and EP1 receptors would also be involved in bladder storage dysfunction after SCI.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation